[The narrator reads out the onscreen text.]

NARRATOR: Question one. Which expression is equivalent to 2 minus 3t? 3 minus 2t, 3t minus 2, negative 2 plus 3t, or negative 3t plus 2? The linear expression 2 minus 3t can be thought of as the sum of two terms: 2 and negative 3t, ie, 2 minus 3t is equal to 2 plus negative 3t. The order of addition doesn't matter. So 2 plus negative 3t is the same as negative 3t plus 2. Therefore, 2 minus 3t is equivalent to the fourth expression negative 3t plus 2.

We can check our solution by substituting a value for t into both expressions. If the expressions are indeed equivalent, then they should both give the same value regardless of the value of t substituted. Here we can see three values of t substituted into both expressions, in each case giving the same value.

[If t = 1, then 2 - 3 × 1 = -1 and -3 × 1 + 2 = -1.

If t = 5, then 2 - 3 × 5 = -13 and -3 × 5 + 2 = -13.

If t = -2, then 2 - 3 × -2 = 8 and -3 × -2 + 2 = 8.]